FRI0510 Long-Term Post Partum Follow-Up of Undifferentiated Connective Tissue Diseases Newly Diagnosed during Pregnancy. (15th July 2016) - Ramoni, V.; Romano, M.; Rocchetti, C.; Vitolo, B.; Beneventi, F.; Cavagnoli, C.; Locatelli, E.; Simonetta, M.; Klersy, C.; Caporali, R.; Montecucco, C.
Abstract : Background: Undifferentiated connective tissue disease (UCTD) is a group of systemic autoimmune conditions not fulfilling the classification criteria for a definite connective tissue disease (CTD). While an average of 20–40% of UCTD patients develop a defined CTD during follow-up, the remaining patients maintain an undefined diseases. Objectives: The objective was to assess flare or differentiation into well-defined CTD of UCTD newly diagnosed during pregnancy and to evaluate the prevalence of obstetric complications in the context of the new diagnosis. Methods: We examined 54 patients with UCTD newly diagnosed during pregnancy, followed during pregnancy and after delivery at our rheumatologic unit. Diagnosis of UCTD was made at the time of pregnancy. Women in their first trimester (T0 ) were screened using a two-step approach using a self-administered 10-item questionnaire, a subsequent testing for rheumatic autoantibodies (ANA, anti-dsDNA, ENA, anticardiolipin antibodies, anti-β2-glycoprotein I antibodies and lupus anticoagulant) and evaluation by a rheumatologist, who made the final diagnosis. The same questionnaire was re-administered at least one year after delivery (T1 ) and the same rheumatic autoantibodies were tested at the same time. Results: Fourty-two patients (77.77%) showed persistence or worsening of symptoms and 45 (83.33%) had at least one positivity for autoantibodies at T1 . The diagnosis of UCTD was confirmed in 29 patients (53.70%). Sixteen (16/54) women (29.62%) received a final diagnosis of another rheumatic disease: 12 patients with systemic lupus erythematosus (22.22%), 2 (3.70%) antiphospholipid syndrome, 1 (1.85%) spondyloarthritis and 1 (1.85%) Behçet disease. Amelioration of symptoms with a resulting unconfirmed diagnosis was seen among 9/54 (16.67%) of them. We then focused on the pregnancy that was ongoing at T0 . We observed some obstetrical complications: 3 miscarriages, 3 fetal loss, 6 hypertensive disorders, 4 intrauterine growth restriction, 6 preterm deliveries and 8 small for gestational age babies. These major obstetrical complications were not significantly different in the three different groups of new diagnoses. Also in the univariate analysis performed through Fisher's test for each single obstetric complication there was no significant difference between groups. Conclusions: The questionnaire is an optimal screening method to detect undiagnosed rheumatic diseases in pregnancy, in particular UCTDs. Furthermore, in spite of their evolution or remission, UCTDs are always associated with negative effects on the outcome of pregnancy. References: Spinillo A, Beneventi F, Epis OM, Montanari L, Mammoliti D, Ramoni V, et al. Prevalence of undiagnosed autoimmune rheumatic diseases in the first trimester of 87 pregnancy. Results of a two-steps strategy using a self-administered questionnaire and autoantibody testing. BJOG An Int J Obstet Gynaecol 2008;115:51–7. Spinillo A, Beneventi F, Ramoni V, Caporali R, Locatelli E, Simonetta M, et al. Prevalence and significance of previously undiagnosed rheumatic diseases in pregnancy. Ann Rheum Dis 2012;71:918–23. Disclosure of Interest: None declared